2021
DOI: 10.1039/d0qm01064b
|View full text |Cite
|
Sign up to set email alerts
|

Inverted perovskite solar cells based on potassium salt-modified NiOX hole transport layers

Abstract: Perovskite solar cells (PSCs) have been attracting increasing attention in recent years because of their exceptional high efficiency with incredible developments. However, the poor contact between hole transport layer (HTL)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Through surface modification of the NiO x film, the interfacial properties can be further improved to adjust the energy level to increase hole transport ability as well as the excellent crystallinity growth of the perovskite film. , Du et al improved the band alignment between NiO x and the perovskite layer by adopting a PTAA interlayer to effectively modify a surface morphology of the solution-processed NiO x film, resulting in the improved V OC and faster charge extraction . Liu et al demonstrated that NiO x films modified with potassium salts improve the perovskite film quality and increase the efficiency of charge extraction capability by reducing the interfacial trap density, leading to enhanced device performance . In addition, self-assembled monolayers can be strong candidates to generate interface modification-induced favorable effects, such as improvement of the affinities of the films by controlling the surface energy and inorganic surface state passivation through chemical bonding, thereby improving device performance. The NiO x film used in PSCs has been fabricated in various ways such as the solution process, atomic layer deposition, pulse laser deposition, vacuum evaporation, and magnetron sputtering .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through surface modification of the NiO x film, the interfacial properties can be further improved to adjust the energy level to increase hole transport ability as well as the excellent crystallinity growth of the perovskite film. , Du et al improved the band alignment between NiO x and the perovskite layer by adopting a PTAA interlayer to effectively modify a surface morphology of the solution-processed NiO x film, resulting in the improved V OC and faster charge extraction . Liu et al demonstrated that NiO x films modified with potassium salts improve the perovskite film quality and increase the efficiency of charge extraction capability by reducing the interfacial trap density, leading to enhanced device performance . In addition, self-assembled monolayers can be strong candidates to generate interface modification-induced favorable effects, such as improvement of the affinities of the films by controlling the surface energy and inorganic surface state passivation through chemical bonding, thereby improving device performance. The NiO x film used in PSCs has been fabricated in various ways such as the solution process, atomic layer deposition, pulse laser deposition, vacuum evaporation, and magnetron sputtering .…”
Section: Introductionmentioning
confidence: 99%
“…28 Liu et al demonstrated that NiO x films modified with potassium salts improve the perovskite film quality and increase the efficiency of charge extraction capability by reducing the interfacial trap density, leading to enhanced device performance. 29 In addition, selfassembled monolayers can be strong candidates to generate interface modification-induced favorable effects, such as improvement of the affinities of the films by controlling the surface energy and inorganic surface state passivation through chemical bonding, thereby improving device performance. 30−32 The NiO x film used in PSCs has been fabricated in various ways such as the solution process, 33 atomic layer deposition, 34 pulse laser deposition, 35 vacuum evaporation, 36 and magnetron sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…Potassium salts, such as KI, KSCN and KNO 3 , and other inorganic salts worked in a similar way to this material. 167 However, distinct from the inorganic salts mentioned above, Zhang et al highlighted the focus of CsBr for inverted PSCs to alleviate interfacial stresses caused by lattice mismatch. 168 The resulting treated device achieved a certified efficiency of 19.7% and favorable stability.…”
Section: Interfacial Engineering In the Inverted Structurementioning
confidence: 99%
“…To fabricate n-i-p b-PSCs with highly efficient PV characteristics (e.g., light collection, photoelectric conversion, and stable output), new strategies must be investigated to improve the photoelectric balance of the RWL while maintaining its properties and processing techniques, and using conventional materials. 5,10,11 In contrast to conventional inorganic hole transport materials (e.g., copper-based semiconductors, metal chalcogenides, carbides, and nitrides), [14][15][16] 2D transition metal dichalcogenides (TMDs) have been regarded as among the most promising PV semiconductor materials because of their high transmittance, excellent carrier mobility, good chemical/environmental stability, and remarkable flexibility. [17][18][19][20][21] There have been extensive studies on organic solar cells (OSCs) that used TMDs such as sulfides, tellurides, and selenides as charge-transport layers.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to conventional inorganic hole transport materials ( e.g. , copper-based semiconductors, metal chalcogenides, carbides, and nitrides), 14–16 2D transition metal dichalcogenides (TMDs) have been regarded as among the most promising PV semiconductor materials because of their high transmittance, excellent carrier mobility, good chemical/environmental stability, and remarkable flexibility. 17–21 There have been extensive studies on organic solar cells (OSCs) that used TMDs such as sulfides, tellurides, and selenides as charge-transport layers.…”
Section: Introductionmentioning
confidence: 99%